Effect of (Al/Ta) co-doped on dielectric properties of CdCu3Ti4O ceramics - Huan Liu; Zhanhui Peng; Yulin Chen; Bi Chen; Di Wu; Lingling Wei; Pengfei Liang; Xiaolian Chao; Zupei Yang (Journal of Advanced Dielectrics)
In this work, dense CdCu3(Al[Formula: see text]Ta[Formula: see text]Ti[Formula: see text]O[Formula: see text] ceramics were prepared by a conventional solid phase method. The effect of Al[Formula: see text]/Ta[Formula: see text] dopants on the dielectric properties of CdCu3Ti4O[Formula: see text] ceramics was systematically investigated. Upon Al[Formula: see text]/Ta[Formula: see text] co-doping, the dielectric properties of CdCu3(Al[Formula: see text]Ta[Formula: see text]Ti[Formula: see text]O[Formula: see text] were significantly enhanced. Particularly, the CdCu3(Al[Formula: see text]Ta[Formula: see text]Ti[Formula: see text]O[Formula: see text] material displays a decent dielectric property, where dielectric constants ([Formula: see text]), loss tangent (tan [Formula: see text]) at a test frequency of 1[Formula: see text]kHz are able to satisfy the application temperature requirement of the Y6R capacitor. Surprisingly, the refined grains resulting from Al[Formula: see text]/Ta[Formula: see text] co-doping lead to heightened resistance at grain boundaries, which is closely associated with enhanced dielectric properties. Meanwhile, the giant dielectric property of the materials can be attributed to the effect of the internal barrier layer capacitance. The obtained results are expected to provide a new idea for obtaining high dielectric constant and low loss tangent in CdCTO-based materials and promote the practical application of such materials.